APPRAISAL OF HUMAN RESOURCE DEVELOPMENT AND PORT OPERATIONS IN SOUTHWESTERN PORTS IN NIGERIA - Kingdom Bello (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This study assessed human resource development and port operations in the Nigerian maritime industry. It examined the organization development, training development and career development and factors that could motivate employees at the southwestern seaports which include Lagos Port Complex and Tincan Island Port Complex. A survey research design was employed, in which both inferential and descriptive statistics were used to analyse 100 questionnaires from the respondents. The result in table 1 shows the relationship between training development and carrier development. It was discovered that there is a relationship between the f statistics (TD=167.515 and CD = 283.707). However, both training and career development are significant (p = 0.000). It can be deduced that training and career development enhance organisational performance. Also the result demonstrates that reasonable income, social security, and pensions serve as the primary motivators for employees, along with decent working conditions, health, safety, and environment. It was concluded that organisational performance is anchored on training development, career development, and employee motivations. These factors increase worker competence and productivity, which in turn improves the organisation's performance in the maritime industry. The maritime industry should prioritise staff development and adopt workplace democracy to motivate workers.